FORMULATION OPTIMIZATION FOR COLON TARGETED DELIVERY OF KATIRA GUM MATRIX TABLETS CONTAINING AZATHIOPRINE (International Journal of Pharmaceutical Sciences and Drug Research, 2013)
Katira gum, a natural polysaccharide resembles guar gum in chemical composition and is susceptible to degradation by colonic microflora. Azathioprine is used in the treatment of inflammatory bowel disease, ulcerative colitis and Crohn’s disease. Present investigation was undertaken to design Katira gum oral colon targeted matrix tablets containing azathioprine, in order to maximize its therapeutic efficacy. Central composite design (software design expert v. 8.0.7.1) was employed to optimize the formulation for maximum drug release in colon. The optimized batch tablets obtained were further coated by Eudragit S100 to minimize the drug release in upper part of GIT. The uncoated matrix tablets released around 20-50% of the drug in the physiological environment of stomach and small intestine but released all its contents in the colon. The coated optimized formulation exhibited a release of only 5-35% in stomach and small intestine and almost all drug in simulated colonic dissolution media. The drug release kinetics followed Korsmeyer-Peppas model, indicating the drug release mechanism through combined diffusion and erosion mechanism. The results suggested that Katira gum can be a good carrier for colon targeting owing to its moderate viscosity, biocompatibility and biodegradability which could be successfully degraded by the microbial flora in the colon.